Potential Co-exposure to Arsenic and Fluoride and Biomonitoring Equivalents for Mexican Children - Jorge H. Limón-Pacheco; Mónica I. Jiménez-Córdova; Mariana Cárdenas-González; Ilse M. Sánchez Retana; María E. Gonsebatt; Luz M. Del Razo (Ubiquity Press, 2018)
Background: Mexico is included in the list of countries with concurrent arsenic and fluoride contamination in drinking water. Most of the studies have been carried out in the adult population and very few in the child population. Urinary arsenic and urinary fluoride levels have been accepted as good biomarkers of exposure dose. The Biomonitoring Equivalents (BE) values are useful tools for health assessment using human biomonitoring data in relation to the exposure guidance values, but BE information for children is limited. Methods: We conducted a systematic review of the reported levels of arsenic and fluoride in drinking water, urinary quantification of speciated arsenic (inorganic arsenic and its methylated metabolites), and urinary fluoride levels in child populations. For BE values, urinary arsenic and fluoride concentrations reported in Mexican child populations were revised discussing the influence of factors such as diet, use of dental products, sex, and metabolism. Results: Approximately 0.5 and 6 million Mexican children up to 14 years of age drink water with arsenic levels over 10 μg/L and fluoride over 1.5 mg/L, respectively. Moreover, 40% of localities with arsenic levels higher than 10 μg/L also present concurrent fluoride exposure higher than 1.5 mgF/L. BE values based in urinary arsenic of 15 μg/L and urinary fluoride of 1.2 mg/L for the environmentally exposed child population are suggested. Conclusions: An actual risk map of Mexican children exposed to high levels of arsenic, fluoride, and both arsenic and fluoride in drinking water was generated. Mexican normativity for maximum contaminant level for arsenic and fluoride in drinking water should be adjusted and enforced to preserve health. BE should be used in child populations to investigate exposure.